Mother Earth, Cultural Authenticity, and Canadian Law - Glass, Matthew (Journal for the Study of Religion, Nature and Culture, 2024)
I can understand that Gill’s commitment to the academic study of religion would lead him to make a strong distinction between the scholarly search for truth and political advocacy—a point he emphasized in his 1997 JAAR debate with Chris Jocks (Gill 1997; Jocks 1997). At the same time, however, scholarly searches for truth in contentious areas might best lead those scholars to acknowledge how their searches fit in with and affect the surrounding contests of the political world, if only to ensure that their work is not appropriated in ways that misconstrue their conclusions.